Plastic Surgery Practice Models and Research Aims under the Patient Protection and Affordable Care Act. Issue 2 (February 2015) - Giladi, Aviram M.; Yuan, Frank; Chung, Kevin C.
<x xml:space="preserve">Abstract</x> Summary: As the health care landscape in the United States changes under the Affordable Care Act, providers are set to face numerous new challenges. Although concerns about practice sustainability with declining reimbursement have dominated the dialogue, there are more pressing changes to the health care funding mechanism as a whole that must be addressed. Plastic surgeons, involved in various practice models each with different relationships to hospitals, referring physicians, and payers, must understand these reimbursement changes to dictate adequate compensation in the future. In this article, the authors discuss bundle payments and accountable care organizations, and how plastic surgeons might best engage in these new system designs. In addition, the authors review the value of a focused and driven health-services research agenda in plastic surgery, and the importance of this research in supporting long-term financial stability for the specialty.